2008
DOI: 10.1002/chem.200801636
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvalene Porphyrins

Abstract: Four tetrathiafulvalene (TTF)-annulated porphyrins 1-4 were synthesized and characterized. All contain a tetraphenylporphyrin (TPP) core onto which four, two, or one TTF subunits were annulated. Absorption and fluorescence spectroscopic studies together with electrochemical investigations reveal that interactions between the porphyrin system and the annulated TTF units take place in solution. The annulation of one or more TTF units to the porphyrin core has a profound effect on the reduction potentials associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 93 publications
1
17
0
Order By: Relevance
“…This is because these derivatives can be used as versatile building blocks to construct a wide range of functional supramolecular materials . In fact, several pyrrole‐annulated TTF derivatives have been synthesized, some of which were successfully applied to construct porphyrins, expand porphyrins, calix[ n ]pyrroles, and rotaxanes, so on . In the particular case of TTF‐calix[4]pyrrole (TTF‐C4P) receptors for the colorimetric detection of nitro‐aromatic explosives, it has been demonstrated that their performance such as binding affinities and colorimetric responsiveness can be dramatically enhanced through electronic modulation of the parent TTF‐pyrrole building blocks used to construct the C4P frameworks .…”
Section: Methodsmentioning
confidence: 99%
“…This is because these derivatives can be used as versatile building blocks to construct a wide range of functional supramolecular materials . In fact, several pyrrole‐annulated TTF derivatives have been synthesized, some of which were successfully applied to construct porphyrins, expand porphyrins, calix[ n ]pyrroles, and rotaxanes, so on . In the particular case of TTF‐calix[4]pyrrole (TTF‐C4P) receptors for the colorimetric detection of nitro‐aromatic explosives, it has been demonstrated that their performance such as binding affinities and colorimetric responsiveness can be dramatically enhanced through electronic modulation of the parent TTF‐pyrrole building blocks used to construct the C4P frameworks .…”
Section: Methodsmentioning
confidence: 99%
“…The calculated conformations of the macrocyclic core planes for the free-base derivative and its Zn(II)-complex were found to be nearly planar, findings that are consistent with the literature data reported earlier. 9,10 The systems were analyzed in accord with the Goutemann four orbital model used to describe the electronic features of ordinary porphyrins. Using this analysis, the molecular orbitals (MOs) of the (TTF) 4 PZn and (TTF) 4 PZn:C 60 Im were characterized by electron density distributions expected for CT molecules.…”
Section: Electrochemistry and Computational Studiesmentioning
confidence: 99%
“…In one case, this was done by annulation of tetrathiafulvalenes (TTFs) at the β-positions of porphyrin, making the resulting molecules extraordinarily electron rich. Hybrid TTF-annulated porphyrins [7][8][9][10][11][12][13] are particularly attractive because they contain both redox active sites and a chromophoric unit contained within a single molecular framework. [14][15][16][17][18][19] In the present study, we report the synthesis of a novel π-extended zinc porphyrin bearing four TTF substituents at its β-positions with 3,5-di-t-butyl-4-hydroxyphenyl groups at mesopositions (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2 . This ranges from the addition of simple alkyl, acyl or aryl substituents [ 13 , 19 , 26 – 28 ] to the preparation of fused ring systems [ 11 , 27 ], to the incorporation of MPTTFs and BPTTFs into more complex molecular architectures such as macrocycles [ 8 9 14 ], calix-pyrroles [ 1 , 10 11 ], calixarenes [ 29 ] and porphyrins [ 30 ]. Note that for MPTTFs, R 1 and R 2 can be either the same or different.…”
Section: Introductionmentioning
confidence: 99%